The Importance of Fundamental Science for Society: The Success Story of Ozone Research - Guy P. Brasseur (Perspectives of Earth and Space Scientists)
Abstract The successful story of ozone research from the discovery of this gas in the laboratory in 1839 to the protection of the stratospheric ozone layer by the Montreal Protocol in 1987 highlights the role and importance of fundamental research. None of the scientists who discovered the chemical nature and properties of ozone, and established its presence in the atmosphere, suspected that humans would be able to destroy a protective stratospheric layer that is essential for life on Earth. None of them had anticipated either that the emissions of pollutants associated with industrial activity and road transportation in urban areas would generate summertime ozone smog events with detrimental health effects and premature mortality. Scientific research has provided the knowledge needed to convince governments to take effective legislation to ban the industrial production of stratospheric ozone depleting agents and reduce the emissions of ozone precursors in the troposphere. This perspective paper calls for enhanced support of a strong fundamental research activity that rewards imagination and protects the scientific community from tight administrative and financial constraints. It highlights the need for scientists to keep a free and independent mind that leads to progress and innovation.